Assessment of drug utilization pattern of antidiabetic drugs in type-2 diabetes outpatient of a tertiary care teaching hospital western Rajasthan - Tanwar, Sumita; Acharya, Aakanksha; Hasan, Najmul (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Glycemic control remains the major therapeutic objective for prevention of target organ damage and other complications arising from diabetes. Poor glycemic control in diabetes mellitus can be prevented by using rational use of oral hypoglycemic agents (OHA). Rational use of the drugs in populations can be effectively evaluated using drug utilization studies. Methods: The present study was conducted in the outpatient departments of General Medicine at Sardar Patel Medical College associated group of PBM Hospital, a tertiary care teaching hospital. It was a cross sectional prospective study carried out over a period of four months from September 2020 to January 2020. Patients were enrolled on the basis of inclusion and exclusion criteria. Results: Total 300 patient prescription patterns were studied, out of which 58.33% were males and 41.66% were females. Most of the patients were in the age group of 51-60 years. Average number of anti-diabetic drugs per prescription was found to be 1.99. biguanides was the most commonly prescribed drug (97%) as mono therapy and combination therapy followed by sulfonylureas (65.6%), DPP 4 inhibitors (24%) Majority of the patients (66%) were on multidrug therapy. Conclusions: Metformin was the most frequently prescribed drug in diabetes. Prescription by Brand name is a matter of concern. Overall, monotherapy was found to be predominant over combination therapy. There was no significant increase in the prescribing of newer oral antidiabetic agents like GLP-1receptor inhibitors and DPP-4 inhibitors. glimepride + metformin combination was the most commonly prescribed combination.